SPECIFIC FEATURES OF ORGANIZING THE EDUCATIONAL- UPBRINGING PROCESS IN GENERAL EDUCATION SCHOOLS (The Journal of Interdisciplinary Human Studies, 2026)
The organization of the educational-upbringing process in general education schools represents a multifaceted challenge encompassing pedagogical, psychological, socio-cultural, and administrative dimensions. This article investigates the specific features that characterize the organization of this process in general education schools, with particular attention to the integration of classical Islamic-Uzbek pedagogical heritage and contemporary educational frameworks. Using a mixed-methods research design involving document analysis, structured classroom observations (n = 45), and teacher interviews (n = 30) across 15 general education schools, the study identifies five core organizational features: (1) the unity of instructional and upbringing components, (2) age-appropriate developmental sequencing, (3) value-based content integration, (4) quality of teacher-student relationships, and (5) institutional-family-community collaboration. The findings indicate that schools successfully implementing an integrative approach drawing on both classical pedagogical wisdom from scholars such as Ibn Sina, Al-Ghazali, and Yusuf Khos Hojib, and modern educational science demonstrate significantly higher student engagement and character development outcomes. These results carry implications for curriculum design, teacher preparation, and school management policy in post-Soviet Central Asian educational contexts.
Keywords: educational-upbringing process; general education schools; pedagogical organization; Uzbek pedagogy; holistic education; educational reform